Novel Quinoline Compound Derivatives of NSC23925 as Potent Reversal Agents Against P-Glycoprotein-Mediated Multidrug Resistance - Quan, Xingping; Du, Hongzhi; Xu, Jingjing; Hou, Xiaoying; Gong, Xiaofeng; Wu, Yao; Zhou, Yuqi; Jiang, Jingwei; Lu, Ligong; Yuan, Shengtao; Yang, Xiangyu; Shi, Lei; et al. (Frontiers in Chemistry, 2019)
Multidrug resistance is a serious problem and a common cause of cancer treatment failure, leading to patient death. Although numerous reversal resistance inhibitors have been evaluated in preclinical or clinical trials, efficient and low-toxicity reversal agents have not been identified. In this study, a series of novel quinoline compound derivatives from NSC23925 were designed to inhibit P-glycoprotein (P-gp). Among them, YS-7a showed a stronger inhibitory effect against P-gp than verapamil, as a positive control, when co-incubated with chemotherapy drugs at minimally cytotoxic concentrations. YS-7a suppressed the P-gp transport function without affecting the expression of P-gp but stimulated the ATPase activity of P-gp in a dose-dependent manner. Next, molecular docking was used to predict the six most probable binding sites, namely, SER270, VAL273, VAL274, ILE354, VAL357, and PHE390. Moreover, YS-7a had no effect on cytochrome P450 3A4 activity and showed little toxicity to normal cells. In addition, combined treatment of YS-7a with vincristine showed a better inhibitory effect than the positive control verapamil in vivo without a negative effect on mouse weight. Overall, our results showed that YS-7a could reverse cancer multidrug resistance through the inhibition of P-gp transport function in vitro and in vivo, suggesting that YS-7a may be a novel therapeutic agent.